We believe in the Holy Spirit - Westhuizen, Henco van der; Ward, Graham (Cascade Books, 2023)
"We believe in the Holy Spirit is a collection of articles reflecting some of the most important ideas in pneumatology in recent years. Although the articles were not written to fit the articles of the Nicene Creed (381), linking these articles to the articles of the creed sheds imaginative light on the development of ideas in theologies of the Spirit." --